2012
DOI: 10.4103/0253-7613.103303
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-inflammatory activity of Typha angustifolia pollen grains extracts in experimental animals

Abstract: Objective:This study was designed to evaluate the anti-inflammatory activity of aqueous and 70% methanolic extracts of pollen grains of Typha angustifolia.Materials and Methods:Female Sprague Dawley rats were used for the study. The acute anti-inflammatory activity of pollen grains of T. angustifolia was studied using the carrageenan as phlogistic agent, whereas its chronic anti-inflammatory effect was investigated by the percentage inhibition of cotton pellet-induced granuloma.Results:Both aqueous and 70% met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…Previous basic studies have demonstrated the effects of Pollen Typhae Angustifoliae on immune system [ 15 ], on coagulation system [ 16 ], and on metabolism [ 17 ]. In addition, anti-inflammatory activity and antioxidant potential of Pollen Typhae Angustifoliae were also reported [ 3 , 18 ]. Another component of Tiaozhi granule is Curcuma longa L. , which mainly has been used as an antihepatotoxic drug [ 4 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous basic studies have demonstrated the effects of Pollen Typhae Angustifoliae on immune system [ 15 ], on coagulation system [ 16 ], and on metabolism [ 17 ]. In addition, anti-inflammatory activity and antioxidant potential of Pollen Typhae Angustifoliae were also reported [ 3 , 18 ]. Another component of Tiaozhi granule is Curcuma longa L. , which mainly has been used as an antihepatotoxic drug [ 4 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to TCM theory, HLP in patients is caused by imbalance of blood stasis; thereafter, Tiaozhi granule aimed to rectify this imbalance. Three components of Tiaozhi granule have been widely applied in TCM for treatment of atherosclerosis, cancer, and inflammatory diseases [ 3 5 ]. Our recent study demonstrated that Tiaozhi granule could upregulate scavenger receptor class B type I (SR-BI) in hepatic cell [ 6 ], which may be one of its therapeutic mechanisms in controlling cholesterol homeostasis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ohkura et al observed that the activation of the intrinsic coagulation pathway by the acidic polysaccharide contributes to the external hemostatic property of Pollen Typhae Angustifoliae , and the components such as flavonoids that possess anticoagulant activity are causative agents when orally administered [22]. Later, anti-inflammatory activity and antioxidant potential of Pollen Typhae Angustifoliae were also reported [15, 23]. Recently, Pollen Typhae Angustifolia was reported to improve insulin resistance in the high-fat diet and low-dose streptozotocin-induced type 2 diabetic rats [24].…”
Section: Discussionmentioning
confidence: 99%
“…Wan Da-Cheng, a grandmaster of Chinese Medicine, according to his long-term clinical experience, proposes that AS and HLP are inseparable, and the pathogenesis of HLP is mainly due to the blood stasis and congestion of arteries and veins by turbidity phlegm, advocating the concept that “ameliorating phlegm and stasis on the one hand, maintaining the liver normal function on the other hand.” He further developed the Tiaozhi granule to treat HLP patients in clinic, which is mainly composed of Pollen Typhae Angustifoliae, Curcuma longa L., and Rhizoma Alismatis . These components are also widely used in traditional Chinese medicine for the effects of antiatherosclerosis, anticancer, anti-inflammatory, and antioxidative activities [1517]. Although various mechanisms have been identified for their therapeutic effects on treatment of clinical patients, the molecular mechanism related to the treatment of HLP and AS patients is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Протизапальну активність виявляють водні та 70 % метанольні екстракти пилку рогозу вузьколис-того [6]. Крім того, муку кореневищ рогозу вузьколи-стого застосовують при запальних процесах кишеч-ника [7].…”
Section: постановка проблеми у загальному ви-гляді актуальність темиunclassified